WORKSHOP DAN PELATIHAN PEMBELAJARAN LESSON STUDI BAGI GURU - Ratni Purwasih; Ika Wahyu Anita; M. Afrilianto (Jurnal Pengabdian Masyarakat Khatulistiwa, 2020)
Professional teachers are one of the determining factors in the success of teaching and learning in the classroom. Designing quality learning tools is the readiness of the teacher to teach. Teacher professionalism is an absolute requirement for the realization of the objectives of national education. Efforts to develop teacher competency should be carried out comprehensively and continuously Improving the quality, capacity, pedagogical-professional competence and fostering the teaching profession (in this case teachers), especially in MTs Cahaya Harapan Cisarua can be done through Lesson study activities. Lesson study is a model of teacher professional development through teaching and learning (learning assessment) collaboratively with a continuous and cycle system based on the principles of collegiality and mutual learning to build learning communities. The basic concept of implementing Lesson Study includes three activities namely; plan-do-see, namely: (1) Planning (planning). (2) Implementation (action) or learning and observation. (3) Reflections on the planning and implementation of the learning. The response of the participants was enthusiastic about this lesson study training.